Propagation Dynamics of Finite-Energy Airy Pulses in a Cubic–Quintic Competing Nonlinear Fiber - Xin Yan; Xingfang Zhang; Fengshou Liu; Zhenghua Li; Liang Xu; Yuanping Li (IEEE Photonics Journal, 2017)
We numerically simulated dynamic propagation of in-phase and out-of-phase finite-energy Airy pulses in anomalous regions of optical fibers and analyzed the effects of cubic–quintic (CQ) competing nonlinearity and separation parameter on evolution properties. Numerical results showed entirely different effects of quintic nonlinearity on in-phase and out-of-phase Airy pulses that vary with different separation parameters. For in-phase Airy pulses, a central quasi-soliton pulse is shed from all finite-energy Airy pulses when separation parameter is certain. CQ competing nonlinearity exhibits profound effects on propagation dynamics of soliton pulses. However, for out-of-phase Airy pulses, two quasi-soliton pulses and more dispersion wave pulses are symmetrically shed from the main lobe of out-of-phase Airy pulses. CQ competing nonlinearity slightly impacts evolution of out-of-phase Airy pulses depending on peak intensity, which varies with propagation distance and unlike in cases of in-phase Airy pulses.